Pengaruh Media Animasi Terhadap Hasil Belajar IPA pada Siswa Kelas IV SD Negeri 101961 Timbang Deli T.A 2022/2023 - Rangkuti, Elviana; Ramadhani, Mastari; Herdyana, Thessa (Medan Resource Center, 2024)
This research aims to determine the effect of using domino card learning media on the learning outcomes of fourth-grade students in the topic of plant structure and function at SD Negeri 101928 Rantau Panjang and SD Negeri 101961 Timbang Deli. A quasi-experimental quantitative approach was employed in this study, with two classes of 20 students each, one serving as the experimental group and the other as the control group. Pretest and posttest questions were used to collect data. The results revealed that the experimental class, which used domino card learning media, achieved a highest score of 92, while the control class, which did not use the media, scored a maximum of 88. These findings indicate a significant positive influence of the domino card learning media on the science learning outcomes of fourth-grade students at SD Negeri 101961 Timbang Deli.